1988
DOI: 10.1111/j.1600-0609.1988.tb00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive treatment improves survival in adult acute lymphoblastic leukemia

Abstract: 20 consecutive adult patients with acute lymphoblastic leukemia were treated with an intense induction regimen including vincristine, doxorubicin, prednisolone, L‐asparaginase and cyclophosphamide. 16 patients (80%) achieved complete remission and were then given CNS prophylaxis and 3 years of maintenance therapy. With minimum follow‐up of 24 months, the median duration of first remission is 37 + months. Out of 10 patients who have completed maintenance therapy, 2 have relapsed after 14 and 22 months, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In this group there were 13 out of 29 patients with known high-risk criteria. These results compare favourably with other studies reported for adult ALL-patients (1)(2)(3)(4)(5)(6)(7)(8)(9). The outcome for patients treated with less intense induction regimen in group 1 and 2 was poor, with a probability of remaining CR of only 4 and 11070, respectively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this group there were 13 out of 29 patients with known high-risk criteria. These results compare favourably with other studies reported for adult ALL-patients (1)(2)(3)(4)(5)(6)(7)(8)(9). The outcome for patients treated with less intense induction regimen in group 1 and 2 was poor, with a probability of remaining CR of only 4 and 11070, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Treatment results in adult patients with acute lymphoblastic leukaemia (ALL) have improved considerably with more aggressive therapy. Remission frequencies of 70-90% with 20 to 50% disease-free survival after 3 yr have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). For subgroups of patients a long-term disease-free survival of around 60% (2.5-7.9) has been achieved.…”
mentioning
confidence: 99%